Role of Human Resource Management Value-Added on Financial Performance Efficiency Management: The Mediating Role of Employee Commitment - Pantih, Suwardhi (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study explores the interconnections among transformational leadership, employee motivation, employee commitment, and financial management efficiency in the Central Sulawesi banking sector, Indonesia. It aims to uncover how transformational leadership and employee motivation impact a company's financial management efficiency and assesses the mediating function of employee commitment in this context. The research encompasses a sample of 396 employees drawn from various Central Sulawesi banks, selected via convenient sampling. Inclusion criteria encompassed a minimum one-year tenure at their current organization and direct exposure to their superiors' leadership styles and familiarity with financial management practices. Data collection entailed a self-administered questionnaire comprising four sections. The first segment gathered demographic data, including age, gender, education, job position, and tenure. The second assessed transformational leadership, employing adapted items from the Multifactor Leadership Questionnaire (MLQ). It scrutinized idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The third section gauged employee motivation, adapting items from the Work Extrinsic and Intrinsic Motivation Scale (WEIMS), covering extrinsic and intrinsic motivation factors. The fourth section measured financial performance efficiency, considering metrics such as stock price, firm innovativeness, and learning orientation. It also assessed employee commitment, comprising affective, continuance, and normative commitment. Responses utilized a Likert-type scale from 1 (strongly disagree) to 5 (strongly agree). A pilot test ascertained questionnaire clarity and comprehensibility. The findings illuminate the intricate web of factors impacting financial management efficiency, underscoring employee motivation and transformational leadership's pivotal roles, mediated by employee commitment. This study enriches practical and theoretical understanding, offering invaluable insights for leaders, managers, and researchers striving to enhance financial management efficiency and organizational performance.